2021
DOI: 10.3389/fcell.2021.657547
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance and Tumor Immune Microenvironment Heterogenicity of m5C RNA Methylation Regulators in Triple-Negative Breast Cancer

Abstract: PurposeThe m5C RNA methylation regulators are closely related to tumor proliferation, occurrence, and metastasis. This study aimed to investigate the gene expression, clinicopathological characteristics, and prognostic value of m5C regulators in triple-negative breast cancer (TNBC) and their correlation with the tumor immune microenvironment (TIM).MethodsThe TNBC data, Luminal BC data and HER2 positive BC data set were obtained from The Cancer Genome Atlas and Gene Expression Omnibus, and 11 m5C RNA methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 61 publications
3
73
1
Order By: Relevance
“…Previous studies showed the Aly/REF export factor (ALYREF) and Y-box binding protein 1 (YBX1) may act as significant readers for m5C, taking part in cancer-related biological processes ( Yang et al, 2017 ; Chen et al, 2019 ). NSUN2 (NOP2/Sun domain family, member 2), a major m5C-modifying methyltransferase (writer) of RNA, is highly expressed in various tumors such as the esophagus, liver, pancreas, cervix, prostate, kidney, bladder, thyroid, and breast cancers ( Okamoto et al, 2012 ; Huang et al, 2021 ). Recently, NSUN2 was reported to promote gastric cancer cell proliferation in a m5C-dependent manner ( Mei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the Aly/REF export factor (ALYREF) and Y-box binding protein 1 (YBX1) may act as significant readers for m5C, taking part in cancer-related biological processes ( Yang et al, 2017 ; Chen et al, 2019 ). NSUN2 (NOP2/Sun domain family, member 2), a major m5C-modifying methyltransferase (writer) of RNA, is highly expressed in various tumors such as the esophagus, liver, pancreas, cervix, prostate, kidney, bladder, thyroid, and breast cancers ( Okamoto et al, 2012 ; Huang et al, 2021 ). Recently, NSUN2 was reported to promote gastric cancer cell proliferation in a m5C-dependent manner ( Mei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… 13 Huang et al discovered 11 m5C regulatory genes related to TNBC neoplasia in triple negative breast cancer (TNBC), which are related to the poor prognosis of NSUN2 and NSUN6 and TNBC. 14 Xue et al study in head and neck squamous cell carcinoma (HNSCC) showed that the m5C regulatory genes MAPK1, HRAS, RAC1, HIST1H4K and HIST1H3C are potential driving genes of HNSCC and are potentially related to the occurrence of HNSCC. 15 In addition, the demethylation of MAP2K3 is related to inflammation and immune regulation in HNSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research showed that m5C-related genes could regulate tumor immune microenvironment in breast cancer ( 40 ). LncRNAs are also known to be involved in regulating tumor-infiltrating lymph cells in malignant tumors ( 41 ).…”
Section: Discussionmentioning
confidence: 99%